Students’ Reading Comprehension of English Textual Literacy Among Zillenial Generation - Rahmawati, Yeni; Khatimah, Khusnul; Rachman, Dzul; Sunarti, Sunarti (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
According to the Indonesian new curriculum which is generally called Kurikulum Merdeka reading comprehension of text becomes a fundamental skill of learning outcomes.Â However, a long time before the new curriculum was released reading skills, especially in learning a foreign language particularly English have always been the main thing. Starting from this condition, this study aimed to describe the studentsâ€™ reading comprehension of English textual literacy among the Zillenial generation. Another goal, of this study, was to identify the studentsâ€™ reasons related to their reading in textual comprehension. This study applied mixed methods both quantitative and qualitative. The design used descriptive statistics and interviews. the instrument used was a test and a list of interviews. the population in this study was 99 students of Public Vocational Schools in Samarinda whereby, overall, this population also became the sample.Â The result was the students in the fair category. The majority of students got a score around 70 which was included as a fair category. This is in line with the school policy of considering minimum passing grades in English subjects. From qualitative data, it was found that the students were helped by the test which was considered as lower-order thinking (LOT). The test was in multiple choice and the topic was familiar. Surprisingly, based on the findings, this Zillenial generation has low literacy as they acknowledged that they donâ€™t have any specific time for doing English literacy except only the teacherâ€™s command. If the topic of the text is considered difficult usually, they will use translator apps to comprehend the text easily.